2022
DOI: 10.1302/2633-1462.33.bjo-2021-0181.r1
|View full text |Cite
|
Sign up to set email alerts
|

Timing and duration of antibiotic prophylaxis is associated with the risk of infection after hip and knee arthroplasty

Abstract: Aims Antibiotic prophylaxis involving timely administration of appropriately dosed antibiotic is considered effective to reduce the risk of surgical site infection (SSI) after total hip and total knee arthroplasty (THA/TKA). Cephalosporins provide effective prophylaxis, although evidence regarding the optimal timing and dosage of prophylactic antibiotics is inconclusive. The aim of this study is to examine the association between cephalosporin prophylaxis dose, timing, and duration, and the risk of SSI after T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Despite the fact that some studies have found that subsequent use of post-operative antibiotics after the initial preoperative dose may not give additional benefit. [1,10,11,14,15,19] However, some other studies have noted that post-operative doses after the initial pre-operative dose have an advantage over preoperative-only doses. [ 3,35,38] So, if we ignore confounding factors like the expertise of the operating surgeon, the operating time, and patient comorbidities, what made the difference between the prevalence of 0.77% of SSIs in our centre and that of other similar centres operating under almost the same conditions?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that some studies have found that subsequent use of post-operative antibiotics after the initial preoperative dose may not give additional benefit. [1,10,11,14,15,19] However, some other studies have noted that post-operative doses after the initial pre-operative dose have an advantage over preoperative-only doses. [ 3,35,38] So, if we ignore confounding factors like the expertise of the operating surgeon, the operating time, and patient comorbidities, what made the difference between the prevalence of 0.77% of SSIs in our centre and that of other similar centres operating under almost the same conditions?…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin, characterized by its comparatively slower tissue permeation, necessitates early administration to ensure adequate concentrations are attained at the surgical site. [3,11] The correlation between Staphylococcus aureus (S aureus) colonization and the risk of periprosthetic joint infection (PJI) is gaining prominence in the orthopaedic literature. Research indicates that patients preparing for orthopaedic surgery exhibit S aureus colonization rates akin to those observed in the broader population.…”
Section: Introductionmentioning
confidence: 99%
“…A single dose of cefuroxime 1.5 g was recommended by nine trusts (8.3%), while other regimens varied very widely across trusts and were distinct for most of the remaining 67 centres (61.5%). This variation is notable, given recent research by Badge et al 26 showing that adequate weight-based dosage and early administration of the prophylactic antibiotics may reduce the risk of SSI in total hip and total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged antibiotic prophylaxis beyond 24 h has been shown to be ineffective at reducing SSIs and may increase antimicrobial resistance [ 40 , 41 ]. A multi-centre prospective study of 19 Australian hospitals found prolonged administration of antibiotics beyond 24 h showed no difference in rates of SSIs for primary TKA and THA [ 42 ]. Prospective surveillance of 2641 coronary artery bypass graft procedures found prolonged antibiotic exposure was a risk factor for antibiotic resistant organism infections [ 40 ].…”
Section: Discussionmentioning
confidence: 99%